Electroconductive moving bed membrane bioreactor (EcMB-MBR) for single-step decentralized wastewater treatment: Performance, mechanisms, and cost - Nutkritta Udomkittayachai (2022)
Membrane bioreactor (MBR) is an advantageous technology for wastewater treatment. However, efficient nutrient removal and membrane fouling mitigation remain major challenges in its applications. In this study, an electroconductive moving bed membrane bioreactor (EcMB-MBR) was proposed for simultaneous removal of organics and nutrients from domestic wastewater. The EcMB-MBR was composed of a submerged MBR, filled with electrodes and free-floating conductive media. Conductive media were introduced to reduce energy consumption in an electrochemical MBR, to improve nitrogen removal, and to mitigate membrane fouling. The results showed that COD, total nitrogen, and total phosphorus removal was up to 97.1 ± 1.4%, 88.8 ± 4.2%, and 99.0 ± 0.9%, respectively, in comparison with those of 93.4 ± 1.5%, 65.2 ± 5.3%, and 20.4 ± 11.3% in a conventional submerged MBR. Meanwhile, a total membrane resistance reduction of 26.7% was obtained in the EcMB-MBR. The optimized operating condition was determined at an intermittent electricity exposure time of 10 min-ON/10 min-OFF, and a direct current density of 15 A/m2. The interactions between electric current and conductive media were explored to understand the working mechanism in this proposed system. The conductive media reduced 21% of the electrical resistivity in the mixed liquor at a selected packing density of 0.20 (v/v). The combination of electrochemical process and conductive media specially enhanced the reduction of nitrate-nitrogen (NO3−-N) through hybrid bio-electrochemical denitrification processes. These mechanisms involved with electrochemically assisted autotrophic denitrification by autotrophic denitrifying bacteria. As a result, 5.2% of NO3−-N remained in the effluent of EcMB-MBR in comparison with that of 29.5% in the MBR. Membrane fouling was minimized via both mechanical scouring and electrochemical decomposition/precipitation of organic/particulate foulants. Furthermore, a preliminary cost analysis indicated that an additional operating cost of 0.081 USD/m3, accounting for 10 – 30% increment of the operating cost of a conventional MBR, was needed to enhance the nitrogen and phosphorus removal correspondingly in the EcMB-MBR.